Evaluation of performance parameters of the extraction condensing type power unit at a combined heat and power plant - Tokarz, Tadeusz (Wydawnictwa AGH, 2006)
Fundamental relationships defining the effectiveness of regeneration processes in steam power stations were precisely formulated. Characteristics of a extraction condensing type power unit with the regeneration systems at a combined heat and power plant were obtained experimentally for a wide range of operating loads. The energy analysis would yield the optimal range of performance parameters of the power unit for the heating and condensing working modes.

We wstępie artykułu uściślono podstawowe zależności w zakresie efektywności procesu regeneracji w siłowni parowej. Następnie na podstawie badań eksperymentalnych przeprowadzonych w szerokim zakresie obciążeń ruchowych zestawiono charakterystyki bloku upustowo-kondensacyjnego elektrociepłowni z funkcjonującym układem regeneracji. W wyniku przeprowadzonej analizy energetycznej określono zakres optymalnych parametrów pracy bloku zarówno dla ciepłowniczego, jak i dla kondensacyjnego trybu pracy.
Ocena efektywności pracy bloku upustowo-kondensacyjnego elektrociepłowni
Mechanics
Bibliografia s. 107.
Keywords: steam power station; power plant; combined heat and power plant; extraction condensing type power unit; regeneration system; siłownia parowa; elektrownia; elektrociepłownia; blok upustowo-kondensacyjny; układ regeneracji